2009
DOI: 10.1080/10934520802515434
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of VOC and BTEX concentration in ambient air around industrial sources in Daegu, Korea

Abstract: Patterns of VOC and BTEX (Benzene, Toluene, Ethylvenzene, and Xylene) distribution at industrial emission sources, proximal residential areas of industrial estates, and ambient air were studied in Daegu, Korea. Daytime and night-time sampling was done at 12 sites and 9 emission sources to provide samples for analyses, using the TO-14 method. Measured BTEX component ratios B/T, T/EB, T/X and EB/X in ambient air were found to be 2.6 g, 11.3 g, 1.0 g and 1.2 g in the residential area; 2.2 g, 11.0 g, 1.0 g and 1.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Based on different BTEX ratios between the urban (2:4:1:2.6) and landfill (3:5:1:2), Zou et al [20] concluded that their BTEX sources are different from each other. Likewise, Choi et al [44] reported that BTEX emission source characteristics of residential (2.6:11.3:1:1.2) and commercial areas (2.2:11:1:1.6) have different from those of the industrial areas (1:14.9:1:1.3). In our study, relative proportion of BTEX averaged as 0.6:5.3:1.0:1.4.…”
Section: Btex Concentrationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on different BTEX ratios between the urban (2:4:1:2.6) and landfill (3:5:1:2), Zou et al [20] concluded that their BTEX sources are different from each other. Likewise, Choi et al [44] reported that BTEX emission source characteristics of residential (2.6:11.3:1:1.2) and commercial areas (2.2:11:1:1.6) have different from those of the industrial areas (1:14.9:1:1.3). In our study, relative proportion of BTEX averaged as 0.6:5.3:1.0:1.4.…”
Section: Btex Concentrationsmentioning
confidence: 94%
“…Diagnostic BTEX composition ratios with ethylbenzene based normalization have been consistently used to identify possible emission sources [20,44,45]. Based on different BTEX ratios between the urban (2:4:1:2.6) and landfill (3:5:1:2), Zou et al [20] concluded that their BTEX sources are different from each other.…”
Section: Btex Concentrationsmentioning
confidence: 99%
“…Based on BTEX ratios in the exhaust gas of gasoline combustion (1.3:4.2:1:3.8), Wang et al (2002) concluded that BTEX sources of urban area (2.9:4.3:1:4.6) and rural area (6.7:11.4:1:4.7) were very similar from traffic-related emission. Choi et al (2009) reported that BTEX emission source characteristics of residential (2.6:11.3:1:1.2) and commercial areas (2.2:11:1:1.6) are different from those of the industrial areas (1:14.9:1:1.3). Durmusoglu et al (2010) measured the BTEX ratios in MSW landfills (0.6:5.3:1:1.4), which shown similar BTEX emission source characteristics with industrial areas.…”
Section: Results and Discussion Toxic Vocs Species Concentrationsmentioning
confidence: 95%
“…It should be found that the HQ of almost all 20 VOCs species, except 1,2-dibromoethane, 1,3-butadiene, and benzene, were by far less than 1 for all studied VOCs, indicating that their concentrations were usually below the level of concern (Ramírez et al 2012). The HQ of 1, (Wang et al 2002) b Guangzhou (Wang et al 2002) c Nanhai (Wang et al 2002) d Choi et al 2009 e Durmusoglu et al 2010 f This study 2-dibromoethane, 1,3-butadiene, and benzene was 17.91, 1.71, and 43.88, respectively, which means that their noncancer risk was at the level of definite concern (McCarthy et al 2009). Moreover, HRs of few VOCs were over 0.1 (potential concern), like 1,2-dichloroethane, carbon tetrachloride, isopropyl alcohol, styrene, and tetrachloroethylene (McCarthy et al 2009).…”
Section: Deterministic Exposure Assessmentmentioning
confidence: 97%
“…The volatile organic compounds (VOCs) that are produced during fuel combustion of vehicle engines contribute 70 to 75% of VOCs in the air of the urban environment [2]. Among the VOCs emitted during fossil fuel combustion are benzene, toluene, ethylbenzene and xylene (BTEX), in which these compounds are the most studied compounds by previous researchers due to health effects [6,7] and as a marker for VOCs exposure [8]. Furthermore, benzene is categorized in group 1 carcinogen compound by the International Agency for Research on Cancer (IARC) [9].…”
Section: Introductionmentioning
confidence: 99%